The Evolving Importance of Insulin Signaling in Podocyte Health and Disease - Lay, Abigail C.; Coward, Richard J. M. (Frontiers in Endocrinology, 2018)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease worldwide, occuring in approximately one-third of diabetic patients. One of the earliest hallmarks of DKD is albuminuria, often occurring following disruptions to the glomerular filtration barrier. Podocytes are highly specialised cells with a central role in filtration barrier maintenance; hence, podocyte dysfunction is a major cause of albuminuria in many settings, including DKD. Numerous studies over the last decade have highlighted the importance of intact podocyte insulin responses in the maintenance of podocyte function. This review summarises our current perspectives on podocyte insulin signalling, highlighting evidence to support the notion that dysregulated podocyte insulin responses contribute towards podocyte damage, particularly during the pathogenesis of DKD.